AGRONOMIC PERFORMANCE OF ROCKET AS A FUNCTION OF PHOSPHORUS FERTILISATION IN A P-RICH SOIL - Nascimento, Camila Seno [UNESP]; Nascimento, Carolina Seno [UNESP]; Cecilio Filho, Arthur Bernardes [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2020)
In intensive vegetable production systems, it is natural to increase nutrient contents in the soil due to the frequent fertiliser applications, especially phosphorus (P). There are few studies on the response of vegetables to phosphate fertilisation under such conditions. In this context, the objective of this study was to evaluate the agronomic performance of rocket as a function of phosphorus fertilisation in a P-rich Rhodic Eutrudox soil. Five P doses (0, 50, 100, 200, and 300 kg ha(-1) P2O5) were evaluated in a randomised complete block design with four replicates. Maximum soil P content and shoot P content at harvest were obtained at a dose of 300 kg ha(-1) P2O5. Rocket responded negatively to P fertilisation. The increase of P doses promoted the decrease of height and yield of the crop.
Keywords: Eruca sativa; Phosphate fertilisation; Mineral nutrition; Productive efficiency